Sleep Quality among Medical Students and its Relationship with Self-reported Skin Complaints: A Cross-sectional Study - Dhaifallah Alenizi; Yousif Abdullatif Albedaiwi; Raed Ayidh Alruwaili; Hanaa El-Sayed Abdel Rahman Bayomy; Shereen Mohamed Olama (Journal of Clinical and Diagnostic Research, 2025)
Introduction: Sleep disturbances are a widespread issue among medical students and have been linked to various negative outcomes, both academically and personally. Sleep plays a crucial role in regulating various aspects of skin physiology, including surface pH, trans-epidermal water loss, blood flow, and skin temperature. Aim: This study aimed to assess the sleep quality and the relationship with skin symptoms among medical students at the College of Medicine, Northern Border University, Arar City, Kingdom of Saudi Arabia. Materials and Methods: The present cross-sectional study was conducted to evaluate the sleep quality of medical students at Northern Border University, Arar, Kingdom of Saudi Arabia, from September 2024 to February 2025. Data included sociodemographic information, including lifestyle factors such as age, gender, academic year, current Grade Point Average (GPA), the self-reported skin complaints questionnaire, which includes skin symptoms commonly reported, and the last section contained the sleep condition indicator for assessing subjective sleep quality. Univariate and multivariate analyses were performed, and statistical significance was set at p<0.05. Results: A total of 317 medical students were enrolled in the study of which 179 (56.5%) were females. The average Sleep Condition Indicator (SCI) of students was 17.7 (±5.7), with 40.4% experiencing insomnia (SCI score <16). Over half reported taking more than 30 minutes to fall asleep, while 219 (70.9%) stayed awake for ≤30 minutes if they awoke at night. About 235 (74.1%) had sleep issues for ≥2 nights a week. The most common skin complaints were dryness in 223 (70.4%) and dandruff 212 (66.9%), with 116 (36.6%) reporting itchiness and 39.7% excoriation. Better sleep quality correlated with never having body odour, burning sensation, dandruff, feeling of disfigurement, ingrown hairs, itching, oily skin, cuticle picking, and tingling skin (p-value<0.05). Conclusion: The current study provided evidence of poor sleep quality among the medical students, especially among medical students in early academic years. There is a strong, positive and significant relationship between many skin symptoms and poor sleep. Medical students need to be taught about good sleep behaviours and get enough sleep to promote healthy skin.